The reception of British aesthetics in Germany : seven significant translations, 1745-1776 - Klemme, Heiner; Kuehn, Manfred (Thoemmes, 2001)
The transfer of intellectual ideas between European countries during the period known as the Enlightenment was largely dependent upon the abilities of translators and philosophers, who had to convey and make comprehensible, complex and new ideas expressed in one language to those who thought and wrote in another. Often, they had to invent or conceive a completely new terminology to express what the British authors intended to say. That many of the terms they introduced are now part of common German is a sign of their abilities. It was through endeavours of men like Spalding, Mylius and Resewit.